IMPLEMENTING AN ONLINE APPLICATION FOR CREATING CHILDREN'S BOOKS IN TEACHING ENGLISH TO YOUNG LEARNERS SUBJECT - Lulud Oktaviani; Suprayogi Suprayogi; Albadri Albadri; Annisa Kurnia Asri (Jurnal Ilmiah Spectral, 2023)
English children's storybooks are real sources for children's language acquisition. A student's preference for reading books is determined by their teachers, who should be able to convey English subjects via a variety of media, including children's storybooks. The majority of English teachers in elementary schools are graduates of the English Education Study Program (EESP) who have completed the Teaching English for Young Learners (TEYL) subject. Thus, this study aims to implement an online learning application known as storyweaver.org.in in Teaching English Young Learners (TEYL) subject for EESP who are teachers want-to-be in the future. The qualitative method is employed here. Overall, the findings showed that planning, implementing, and evaluating can be three stages in using storyweaver.org.in in a classroom. Creating and using storybooks occurred to improve Foreign Language skills and cultural customs for young learners who find that storybooks are simple and pleasing methods to learn their culture.